Behavioural risk factors associated with ischemic heart disease among population attending selected cardiac hospitals of Kathmandu, Nepal
Background and Aims: Ischemic Heart Disease (IHD) is the number one cause of morbidity and mortality among the in-patient of different cardiac hospital of developing countries like Nepal. The prevalence of IHD is high with significant associated risk factors that include tobacco use, history of hypertension, family history and age. Though IHD can cause life-threatening conditions like myocardial infarction, yet it is preventable disease. The objective of the study was to study the risk factors associated with ischemic heart diseases among population attending selected cardiac hospitals of Kathmandu. Methods: Hospital- based pair matched case-control was conducted among the patients with IHD at Manmohan Cardiothoracic Vascular and Transplant Centre (MCTVC) and Shahid Gangalal National Heart Center (SGNHC). Non- random purposive sampling technique was applied and sample size was calculated as 105 (35 cases and 70 controls). Case and control were matched with age (Å